TERDAPAT KETIMPANGAN DISTRIBUSI PENDAPATAN PADA KELUARGA MISKIN (STUDI KASUS DI KECAMATAN KEDUNGBANTENG KABUPATEN BANYUMAS) - Dijan Rahajuni; Endang Sri Gunawati; Emmy Saraswati (EKO-REGIONAL, 2014)
Study with the title “ Income Distribution and The Factors that Influence toward Low Economic Society on Kedungbanteng District, Banyumas” case study on low economic family that receive Woman Loan System (Simpan Pinjam Perempuan)  at District Development Program. The aims of this research is to determine and analyze income distribution  and factors that influence of its. This reasect use survey method toward three villages as sample, which are have the furthermost distance from central district (Melung village), middle (Karangnangka village), and the nearest (Kedungbanteng village). The respondent is society, specifically woman that receive Woman Loan System (Simpan Pinjam Perempuan) at District Develompent Program. This research is quantitative descriptive analyzing and used gini index and double linear regression. The result of analysis shows that Income distribution from business activity who have receive loan woman system shows that Karangnangka and Melung classified into low rate of imbalance distribution, otherwise Kedungbanteng classified into high rate imbalance distribution and holistically imbalance distribution on Kedungbanteng include in high rate. Based on regression coefficient factor that have influence mostly in order are long time of business, education, and loan capital, family dependent do not influence toward rate of income. This research suggest to handling event to empower the knowledge, such as entrepreneur skill and the parties that should be more selective when giving loan business.Keywords: District Development Program , ProgramSimpan Pinjam Perempuan, gini index,